(untitled) (Revista Científica Interdisciplinaria Investigación y Saberes, 2023)
Playfulness represents a kind academic process in the teaching practice because the characteristics of learning allow it to be conceived as a pedagogical strategy that promotes meaningful learning. The general objective of this research was to strengthen the learning of reading in the third grade of the Santa Ana Educational Institution through play as a pedagogical strategy. The approach is qualitative, of an interpretative type and with an action research design. The population is formed by two teachers and the proposal is implemented in third grade students. The techniques used were the interview, participant observation, diagnostic test and survey; the instruments were represented in the field diary, questionnaire and interview guide. Among the results obtained are the fulfillment of the three objectives, as well as the design and implementation of the proposal which left significant learning in the students. It was concluded that it is substantial to develop playfulness as a learning strategy that allows a style of apprehension of knowledge, to promote autonomy, since it facilitates the assimilation of new knowledge, ideas based on their own meanings and the construction of their own harmonious learning environment, in which the student is autonomous.